Taxonomy of Epeorus frisoni (Burks) and a key to New England species of Epeorus - Burian, Steven K.; Swartz, Beth I.; Wick, Philip C. (International advances in the ecology, zoogeography and systematics of mayflies and stoneflies. University of California Publications in Entomology, 2008)
Keywords: dept.bio; faculty_collection; ⛔ No DOI found

The Songbirds Bible: A Visual Directory of 100 of the Most Popular Songbirds in North America - Proctor, Noble S. (Ronnie Sellers, 2006)
Keywords: Identification; Identification; Birdsongs; North America; Songbirds; dept.bio; faculty_collection

A Field Guide to North Atlantic Wildlife: Marine Mammals, Seabirds, Fish, and Other Sea Life - Proctor, Noble S.; Lynch, Patrick J. (Yale University Press, 2005)
Keywords: Atlantic Coast (Canada); Atlantic Coast (U.S.); Identification; Identification; Marine algae; Identification; Marine animals; Marine animals; dept.bio; faculty_collection

A Revision of the Genus Leptophlebia Westwood in North America (ephemeroptera:leptophlebiidae:leptophlebiinae) - Burian, Steven K. (Bulletin (Ohio Biological Survey) ; new ser., v. 13, no. 3, 2001)
Keywords: Classification; Identification; Leptophlebia; Leptophlebia; North America; dept.bio; faculty_collection

A comparison of the relative abundance and size of Juvenile winter flounder, Pseudopleuronectes americanus, in natural intertidal and anthropogenically altered marina habitats - Carlson, J.K.; Mroczka, M.E.; Randall, T.A.; Pellegrino, P.E. (Journal of Northwest Atlantic Fishery Science, 2000)
The relative abundance and size distributions of juvenile winter flounder, Pseudopleuronectes americanus, were compared in two areas; an anthropogenically altered marina basin and a natural intertidal flat habitat. Winter flounder were sampled from March through November 1990-95 with a 1.0 m beam trawl. No significant difference was observed in catch-per-unit-effort between areas but significant differences were found between seasons. Relative abundance (number of flounder/m2) increased from spring (0.007 marina and 0.011 intertidal flats) to summer (0.059 marina and 0.051 intertidal flats) and then declined slightly in the autumn (0.047 marina and 0.027 intertidal flats). Relative abundance was similar between areas from 1990-95 but differed between years. Length frequency distributions of winter flounder were similar between areas for all seasons but mean sizes were statistically different in summer. These results suggest that juvenile winter flounder are equally abundant in both natural intertidal habitats and marina basins, indicating that both could serve as nursery areas. However, more specific research is required to resolve the relative importance of marinas and the factors involved in utilization of each habitat.
Keywords: Clinton Harbor; Connecticut; Flounder; Intertidal flats; Marina; Nursery; Pseudopleuronectes americanus; United States; dept.bio; ecological impact; intertidal environment; marina; nursery ground; relative abundance; size distribution

Life history aspects of the mayfly Siphlonurus typicus (Ephemeroptera: Siphlonuridae) with a new application for measuring nymphal development and growth - Kosnicki, E.; Burian, S. (Hydrobiologia, 2003)
Little is known about the life history of mayflies that inhabit temporary ponds. The purpose of this study was to observe and quantify life histories attributes of Siphlonurus typicus, which is known to reside in temporary ponds. Weekly samples of nymphs were taken from two temporary ponds in eastern Connecticut from March to June, 1999. Individuals were graded into 11 maturity classes, based on developmental characteristics, as a means of predicting population maturity rates. Head capsule widths (HCWs) were used to determine if growth occurred between maturity classes. Degree days were found to be an excellent predictor for population maturity (r2 = 0.963, p < 0.0001). Nymphs that hatched earlier in the year had larger HCWs than nymphs that hatched later in the year, possibly because of different temperature regimes. The University of Connecticut Forest pond (UCF) population matured faster than the Merrow Meadows pond (MER) population, but both sexes of the UCF population tended to be smaller than their counter parts from the MER population. Sex ratios were female bias for the UCF population (1.35:1), but were not different for the MER population. Adult emergence and mating occurred from 27 May to 21 June. There was a positive relationship between number of eggs per female and female body length. Oviposition at both sites occurred directly on the ponds, pond inlets, and outlets, indicating that pond populations were the result of local migrants as well as permanent residents. Temperature was a determining factor of maturity and fecundity for Siphlonurus typicus.
Keywords: Age classes; Arthropoda; Biodiversity; Ephemeroptera; Growth rates; Invertebrata; Marine biology; Mating behavior; Maturity; Maturity rates; Mayflies; Ponds; Population statistics; Siphlonuridae; Siphlonurus; Siphlonurus typicus; Swarming; dept.bio; ephemeral pool; growth; larval development; life history; mayfly; swarming

Selecting appropriate controls in studies of owl nest-site selection (reply to Marks) - Bosakowski, T.; Smith, D.G. (Journal of Field Ornithology, 2001)
Marks (2001) is critical of our study of nest-site selection in Great Horned Owls (Bubo virginianus) because we compared our data from owl nests with data from random points rather than from unused stick nests. We argue that Great Horned Owls have so many options for nesting in eastern forests that there is little constraint on nest-site selection. Therefore, their choice of nest sites is determined largely by vegetation characteristics in the surrounding landscape, and comparison of owl nests with random points is the best way to assess nest-site selection. Furthermore, we believe that use of unused nests as controls, as advocated by Marks, is biased because control nests will have many of the same characteristics as nests used by owls.
Keywords: Bubo virginianus; Strigiformes; dept.bio

Habitat, food habits, and productivity of Northern Goshawks nesting in Connecticut - Becker, T.E.; Smith, D.G.; Bosakowski, T. (Studies in Avian Biology, 2006)
We documented active nests of the Northern Goshawk (Accipiter gentilis) at 16 different areas in Connecticut from 1997-1999. A total of 176 prey individuals were identified from remains found under goshawk nests and prey-plucking posts. Birds represented the dominant component of diets (70.5%) with a lower contribution from mammals (29.5%). Overall, Connecticut goshawk diets were dominated by sciurids and Ruffed Grouse (Bonasa umbellus). Productivity calculated from 15 known nesting attempts totaled 32 young for an average of 2.13 young per nesting attempt (range 1-4 young). Goshawks nested in large tracts of mature forests with high levels of canopy cover (82%). The nest site topography was consistent with previous studies finding that goshawks avoid southern slopes. Tree densities in the larger size classes and basal area were characteristic for mature forest. Goshawks constructed their nests in large diameter trees, which averaged 41.7 cm in diameter at breast height. Patch size of contiguous forests surrounding goshawk nests revealed a very high mean of 324.5 ha, thus suggesting that large forest patch size may be important for nesting by this forest interior species. Analysis of 202 ha circles centered on each nest revealed that total forest cover averaged 156.1 ha, which was comprised of 65.2 ha for conifer forest, 75.6 ha for deciduous forest, and 17.4 ha for mixed forest. Overall, the post-fledgling family areas for these nests were dominated by forest cover (>75%). Our results suggest that goshawks usually prefer isolation and little human disturbance at the nest site, but some exceptions were noted. Given the highly fragmented and urbanized landscape of Connecticut, we suggest that goshawk management should focus on providing large tracts of mature forest at least 300 ha in extent.
Keywords: Accipiter; Accipiter gentilis; Aves; Bonasa umbellus; Coniferophyta; Connecticut; Forest; Fragmentation; Habitat; Mammalia; Nest sites; Northern Goshawk; Prey; Productivity; Sciuridae; Site fidelity; dept.bio

Ecology of the Northern Goshawk in the New York-New Jersey Highlands - Bosakowski, T.; Smith, D.G. (Studies in Avian Biology, 2006)
Evidence suggests that the Northern Goshawk (Accipiter gentilis) was once extirpated in the New York-New Jersey Highlands, but has recolonized the Highlands in the 1960s and 1970s following a dramatic reforestation in the 20th century. The reforestation produced large tracts of contiguous mature forest, which appear to be a primary habitat requirement of this species. Most goshawk nests in the Highlands were found deep in remote forest areas where nest sites are typically distant from human habitation and paved roads. Nest trees were almost always built in co-dominant or dominant trees of the stand, but were seldom built in the largest tree of the nesting stand. Canopy cover is very high (90%) and shrub cover is often reduced or nearly devoid (28.3%) at goshawk nest sites. Ruffed Grouse (Bonasa umbellus) appears to be the most common prey, but other predominant bird species in diets of Highlands goshawks included the Blue Jay (Cyanocitta cristata), Mourning Dove (Zenaida macroura), Rock Dove (Columba livia), and blackbirds. Sciurids, including eastern chipmunks (Tamias striatus), red squirrel (Tamiasciurus hudsonicus), and gray squirrel (Sciurus carolinensis) were also important components of goshawk diets from the Northeast. Highlands goshawks had a mean prey weight of 365.8 g, with bird prey averaging 332.3 g and mammal prey averaging 442.9 g. In the Highlands, productivity calculated from 36 nesting attempts averaged 1.4 young per nest, lower than found in two Connecticut studies (1.75 and 2.13). Although the goshawk is generally considered to be a permanent resident, dozens of northeastern hawk migration observation stations reveal a small, but distinct, fall migration during non-invasion years. Breeding bird atlas data confirm that the goshawk is rare in New Jersey, moderately rare in Pennsylvania (mostly northern), and numerous in New York. Various factors impacting Highlands goshawks are discussed including interspecific competition, lack of reserves, timber harvesting, tree diseases, and human disturbance factors.
Keywords: Accipiter gentilis; Aves; Bonasa umbellus; Columba livia; Competition; Cyanocitta cristata; Food-niche overlap; Forestry; Habitat; Mammalia; Migration; Nest sites; New Jersey; New York; Northern Goshawk; Prey; Productivity; Sciuridae; Sciurus carolinensis; Site fidelity; Tamias striatus; Tamiasciurus hudsonicus; Zenaida macroura; dept.bio

Ethnobotany and the loss of traditional knowledge in the 21st century - Ramirez, C.R. (Ethnobotany Research and Applications, 2007)
Keywords: dept.bio

Etnobotánica y la pérdida de conocimiento tradicional en el siglo 21 - Ramirez, C.R. (Ethnobotany Research and Applications, 2007)
Keywords: dept.bio

Ephemeroptera (Mayflies) - Burian, S.K. (Encyclopedia of Inland Waters, 2009)
Mayflies are members of a small, but diverse order of aquatic insects that dates back some 290. My. Mayflies are widely distributed on all continents and most large islands. Currently, the order contains about 3100. species distributed among 42 extant families. Adults are fully terrestrial and short lived, but the aquatic nymphs can live for more than a year and are important components of nutrient and energy pathways in a wide range of aquatic habitats. Higher classification and phylogeny of the mayflies are still in a state of flux, but evidence is accumulating providing stronger support for some groups. Alpha-level taxonomy still remains a problem and much work remains to be done in some genera and in some parts of the world. Extensive morphological studies have provided a solid base of knowledge, but similarly intense physiological, histological, and immunological studies are needed. Much work has been done on the ecology of genera and some species. Much finer scale ecological studies are needed to better understand the importance of small-scale ecological interactions among instars of the same and different species. Globally, there are many surveys in progress to document and map the occurrence and distribution of species. This work is critical to developing conservation strategies for mayflies and other vulnerable aquatic species. © 2009 Elsevier Inc. All rights reserved.
Keywords: Biogeography; Biology; Conservation; Ecology; Ephemeroptera; Life history; Mayfly; Phylogeny; Taxonomy; dept.bio

Microbial diversity of boron-rich volcanic hot springs of St. Lucia, Lesser Antilles - Stout, L.M.; Blake, R.E.; Greenwood, J.P.; Martini, A.M.; Rose, E.C. (FEMS Microbiology Ecology, 2009)
The volcanic Sulphur Springs, St. Lucia, present an extreme environment due to high temperatures, low pH values, and high concentrations of sulfate and boron. St. Lucia offers some unique geochemical characteristics that may shape the microbial communities within the Sulphur Springs area. We chose six pools representing a range of geochemical characteristics for detailed microbial community analyses. Chemical concentrations varied greatly between sites. Microbial diversity was analyzed using 16S rRNA gene clone library analyses. With the exception of one pool with relatively low concentrations of dissolved ions, microbial diversity was very low, with Aquificales sequences dominating bacterial communities at most pools. The archaeal component of all pools was almost exclusively Acidianus spp. and did not vary between sites with different chemical characteristics. In the pool with the highest boron and sulfate concentrations, only archaeal sequences were detected. Compared with other sulfur springs such as those at Yellowstone, the microbial diversity at St. Lucia is very different, but it is similar to that at the nearby Lesser Antilles island of Montserrat. While high elemental concentrations seem to be related to differences in bacterial diversity here, similarities with other Lesser Antilles sites suggest that there may be a biogeographical component as well. © 2009 Federation of European Microbiological Societies. Published by Blackwell Publishing Ltd. All rights reserved.
Keywords: Acidianus; Aquificales; Archaea; Archean; Atlantic Ocean; Atlantic islands; Bacteria; Bacteria (microorganisms); Biodiversity; Boron; Caribbean Islands; DNA, Archaeal; DNA, Bacterial; Extreme environments; Geochemistry; Hot Springs; Lesser Antilles; Microbial communities; Phylogeny; RNA, Ribosomal, 16S; Saint Lucia; Sequence Analysis, DNA; Sulfur springs; Windward Islands [Lesser Antilles]; article; bacterium detection; boron; concentration (parameters); controlled study; dept.bio; geochemistry; high temperature; microbial community; microbial diversity; molecular analysis; molecular cloning; nonhuman; nucleic acid analysis; nucleotide sequence; pH; priority journal; ribosome RNA; sulfate; thermal spring; volcanic landform

Estrogen dependent growth inhibitory effects of tamoxifen but not genistein in solid tumors derived from estrogen receptor positive (ER+) primary breast carcinoma MCF7: single agent and novel combined treatment approaches. - Nobert, Gayle S; Kraak, Martha M; Crawford, Sarah (Bulletin du cancer, 2006)
While many studies have documented tamoxifen's benefits as an adjuvant therapy in the treatment and prevention of recurrent breast cancer in estrogen receptor positive (ER+) breast carcinoma, this beneficial effect may decrease with long-term tamoxifen use. This experimental study was designed to compare the cytotoxic responses of ER+ primary breast cancer solid tumors derived from the MCF7 cell line to experimental therapeutics, including genistein, tamoxifen, all-trans retinoic acid (ATRA) and parthenolide in the presence and absence of exogenous beta-estradiol. The results of this study suggest that the growth inhibitory effects of tamoxifen, were dependent on beta-estradiol levels. In contrast, the cytotoxic effects of the isoflavone soy derivative, genistein, were observed to be independent of exogenous estrogen. Moreover, combined therapy using tamoxifen and genistein produced enhanced cytotoxic effects also independent of beta-estradiol levels. Additional studies involving the use of the novel agents all trans retinoic acid (ATRA) and parthenolide produced notable tumor responses and combined effects that were also estrogen-independent. Overall, these preclinical research findings suggest possible clinical applications suggesting that genistein might be a useful clinical adjuvant, particularly in post-menopausal women in whom breast cancer occurs more frequently. Moreover, this research suggests that combined treatment approaches involving the use of tamoxifen in conjunction with agents that inhibit NFkappaB pathway signaling, such as parthenolide and genistein, warrant further study.
Keywords: *Antineoplastic Combined Chemotherapy Protocols/tu [Therapeutic Use]; *Breast Neoplasms/dt [Drug Therapy]; *Genistein/tu [Therapeutic Use]; *Neoplasms, Hormone-Dependent/dt [Drug Therapy]; *Tamoxifen/tu [Therapeutic Use]; Anticarcinogenic Agents; Anticarcinogenic Agents/tu [Therapeutic Use]; Antineoplastic Agents, Hormonal; Antineoplastic Agents, Hormonal/tu [Therapeutic Use]; Antineoplastic Combined Chemotherapy Protocols; Breast Neoplasms; Breast Neoplasms/ch [Chemistry]; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Resistance, Neoplasm; Drug Resistance, Neoplasm/de [Drug Effects]; Estradiol; Estradiol/pd [Pharmacology]; Female; Genistein; Humans; Neoplasms, Hormone-Dependent; Neoplasms, Hormone-Dependent/ch [Chemistry]; Receptors, Estrogen; Sesquiterpenes; Sesquiterpenes/tu [Therapeutic Use]; Spheroids, Cellular; Spheroids, Cellular/de [Drug Effects]; Tamoxifen; Tretinoin; Tretinoin/tu [Therapeutic Use]; antineoplastic agent; antineoplastic hormone agonists and antagonists; article; breast tumor; chemistry; dept.bio; dose response; drug effect; drug resistance; estradiol; estrogen receptor; female; genistein; human; multicellular spheroid; neoplasm; parthenolide; retinoic acid; sesquiterpene; tamoxifen; tumor cell line; ⛔ No DOI found

Biological identifications of mayflies (Ephemeroptera) using DNA barcodes - Ball, Shelley L; Hebert, Paul D N; Burian, Steven K; Webb, J M (Journal of The North American Benthological Society, 2005)
We tested the efficacy of DNA barcodes in identifying mayfly species primarily from the northeastern United States and central Canada. We sequenced a 630-base-pair segment of the mitochondrial gene, cytochrome c oxidase 1 (COI), from 1 individual of each of 80 species to create a reference sequence profile. We used these reference sequences to identify 70 additional specimens representing 32 of the species that were in the profile. DNA barcodes correctly identified 69 of the 70 test specimens. The sole exception was an individual identified morphologically as Maccaffertium modestum that showed deep genetic divergence from other M. modestum specimens. Mean sequence divergence within species was 1%, whereas mean divergence among congeneric species was an order of magnitude greater (18%). We conclude that DNA barcoding can provide a powerful tool for mayfly species identification. © 2005 by The North American Benthological Society.
Keywords: Aquatic invertebrates; COI; Canada; DNA; Ephemeroptera; Invertebrata; Maccaffertium; Mayfly; North America; Species identification; United States; Western Hemisphere; World; aquatic organism; dept.bio; identification method; mayfly; mtDNA

Caching behavior by wintering northern saw-whet owls, aegolius acadicus - Devine, Arnold; Smith, Dwight G (Canadian Field-Naturalist, 2005)
We observed 16 instances of caching behavior by Northern Saw-whet Owls in southern Connecticut between 30 October and 29 March over a 23-year period 1982 to 2004. Caches consisted of a single prey item in 13 instances and two prey items in three instances. Prey was cached either directly beneath the owl or from 5-28 cm distant, always on the same branch on which the owl was roosting. Observations of cached prey marked in the morning suggested that it was consumed after 14:30 in the afternoon of the same day. Such a delay indicated a true cache rather than delayed feeding.
Keywords: Aegolius acadicus; Caching behavior; Connecticut; North America; Northern Saw-Whet Owl; Strigiformes; United States; caching; dept.bio; marking method; prey capture; raptor; roosting

Summer diet of the peregrine falcon in faunistically rich and poor zones of Arizona analyzed with capture-recapture modeling - Ellis, David H; Ellis, Catherine H; Sabo, Beth Ann; Rea, Amadeo M; Dawson, James W; Fackler, James K; Larue, Charles T; Grubb, Teryl G; Schmitt, John; Smith, Dwight G; Kery, Marc (The Condor, 2004)
We collected prey remains from 25 Peregrine Falcon (Falco peregrinus) territories across Arizona from 1977 to 1988 yielding 58 eyrie-years of data. Along with 793 individual birds (107 species and six additional genera), we found seven mammals and nine insects. In addition, two nestling peregrines were consumed. We found a larger dependence upon White-throated Swifts (Aeronautes saxatalis) and birds on migration in northern Arizona, while in southeastern and central Arizona average prey mass was greater and columbiforms formed the largest dietary component. In northern, central, and southeastern Arizona, 74, 66, and 56 avian prey taxa, respectively, were recorded. We used capture-recapture modeling to estimate totals of 111 ± 9.5, 113 ± 10.5, and 86 ± 7.9 (SE) avian taxa taken in these same three areas. These values are counterintuitive inasmuch as the southeast has the richest avifauna. For the entire study area, 156 ± 9.3 avian taxa were estimated to be taken by peregrines.
Keywords: Aeronautes; Aeronautes saxatalis; Aeronautes saxatatilis; Arizona; Aves; Columbiformes; Diet; Falco; Falco peregrinus; Galliformes; Hexapoda; Insecta; Mammalia; Peregrine Falcon; Peregrinus; Prey; Vertebrata; dept.bio

Life stage descriptions, taxonomic notes, and new records for the mayfly family Leptohyphidae (Ephemeroptera) - Baumgardner, David E.; Burian, Steven K.; Bass, David (Zootaxa, 2003)
Keywords: dept.bio

Taxonomy of Eurylophella coxalis (McDunnough) with notes on larval habitat and behavior (Ephemeroptera:Ephemerellidae) - Burian, Steven K (Journal of The North American Benthological Society, 2002)
Larval stages have been associated for all of the known species of Eurylophella in eastern North America except for E. coxalis. The larva of E. coxalis is described herein from a reared series of specimens. Adults are redescribed and eggs are described for the 1st time, as are notes on larval habitat and behavior. Association of E. coxalis completes our knowledge of the life stages of a presumed different species, Dentatella bartoni, which was previously known only from the larval stage. This larva is now determined to be the larval stage of E. coxalis. Further, characters used to diagnose Dentatella danutae have shown that this taxon is not different from what has been called D. bartoni. Thus, Dentatella bartoni (Allen) and D. danutae McCafferty are now placed as subjective junior synonyms of E. coxalis. A conservative criterion requiring that apomorphic characters be discernable in both larval and adult life stages is proposed for recognizing mayfly genera when knowledge of life stages and/or the phylogenetic nature of diagnostic characters is incomplete. Field and laboratory observations of live E. coxalis larvae show this species to be associated with cold, swift, alkaline streams containing coarse inorganic substrates with well-developed periphyton.
Keywords: Apus apus; D. bartoni; D. danutae; Dentatella; Dentatella bartoni; Dentatella danutae; E. coxalis; Ecology; Ephemerellidae; Ephemeroptera; Eurylophella; Eurylophella coxalis; Taxonomy; behavior; dept.bio; habitat; larva; taxonomy

Developmental expression of a voltage-dependent potassium channel (Kv3.1) in auditory neurons without cochlear input. - Feng, Jane; Morest, D Kent (Journal of Neuroscience Research, 2001)
Kv3.1, a voltage-dependent potassium channel, has two forms, -a and -b, which differ in expression during development and at the onset of function in the auditory system. To determine whether cochlear nerve input could affect the expression of these two forms, cultures of the developing cochlear nucleus were explanted in the absence of the cochlear nerve at the beginning of cell migration (Hamburger-Hamilton stage 28-30), while neuroblasts continued to migrate onto the culture substrate. After 8, 15, and 22 days in vitro (three survival groups), cultures were immunostained with antibodies recognizing either both forms of Kv3.1 or only the -b form. Only young and newly migrated nerve cells were sampled. In the three survival groups, all nerve cells expressed Kv3.1, among which only 50% or less expressed the -b form. Some of the more differentiated multipolar cells expressed the -b form, but most were labeled with the antibody that recognizes both forms. Thus, in the absence of peripheral input, both forms of Kv3.1 appear at stages very early in development, although not all cells necessarily coexpress both forms. These results agree with other observations in the chick embryo in situ. They are consistent with previous work implicating Kv3.1 in cell migration during early development.
Keywords: *Cell Differentiation/ph [Physiology]; *Cell Movement/ph [Physiology]; *Cochlear Nerve/em [Embryology]; *Cochlear Nucleus/em [Embryology]; *Gene Expression Regulation, Developmental/ph [Physiology]; *Neurons/me [Metabolism]; *Neuropeptides/me [Metabolism]; *Potassium Channels, Voltage-Gated; *Potassium Channels/me [Metabolism]; Age Factors; Animals; Cell Compartmentation; Cell Compartmentation/ph [Physiology]; Cell Differentiation; Cell Movement; Cell Size; Cell Size/ph [Physiology]; Cells, Cultured; Cells, Cultured/cy [Cytology]; Cells, Cultured/me [Metabolism]; Chick Embryo; Chicken embryo; Cochlear Nerve; Cochlear Nerve/me [Metabolism]; Cochlear Nucleus; Cochlear Nucleus/cy [Cytology]; Cochlear Nucleus/me [Metabolism]; Cochlear nucleus; Denervation; Gene Expression Regulation, Developmental; Immunohistochemistry; Neurons; Neurons/cy [Cytology]; Neuropeptides; Nucleus magnocellularis; Potassium Channels; Potassium Channels, Voltage-Gated; Protein Isoforms; Protein Isoforms/me [Metabolism]; Sensory Deprivation; Sensory Deprivation/ph [Physiology]; Shaw Potassium Channels; Tissue culture; amino terminal sequence; animal cell; article; auditory nervous system; cell differentiation; cell migration; cell survival; chicken; cochlear nucleus; dept.bio; immunohistochemistry; magnocellular nucleus; nonhuman; potassium channel; priority journal; protein expression; tissue culture

Use of subtidal habitat by the asian shore crab hemigrapsus sanguineus in long island sound - Gilman, Michael; Grace, Sean (Northeastern Naturalist, 2009)
Hemigrapsus sanguineus Asian Shore Crab is an introduced but now common crab found intertidally along the Connecticut coastline. Little is known of its subtidal occurrence. This species was found to be seasonally abundant subtidally, at depths varying from 1.33.9 m, during a 2-year study conducted within a commercial marina in Clinton Harbor, CT. Hemigrapsus sanguineus was trapped at three subtidal locations, with highest concentrations observed during the winter. A total of 2020 crabs were caught: 1255 males, 741 females, and 24 crabs that were 9 mm or smaller and sexually indistinguishable. Large males with carapace widths between 4548 mm were captured at all three locations. These sizes are among the largest reported for this species. This work documents year-round use of subtidal habitat by Asian Shore Crab in Long Island Sound.
Keywords: Decapoda (Crustacea); Hemigrapsus sanguineus; dept.bio; peer-reviewed

Abstract A57: Lipid extract from the ostrich fern Matteucia struthiopteris displays potent anti-cancer effects in microtumors from human malignant cell lines via disruption of actin cytoskeleton - Crawford, Sarah; Penarreta, Rafaella; Diamond, Deanna (Cancer Prevention Research, 2008)
Keywords: dept.bio

Tissue organizing structure and therapeutic methods - Crawford, Sarah; Potter, Herbert; Herbert, Tasino (2008)
Keywords: dept.bio; ⛔ No DOI found

Fragmentation of colonial ascidians: Differences in reattachment capability among species - Bullard, Stephan; Sedlack, Betsy; Reinhardt, James F; Litty, Carolyn; Gareau, Keith; Whitlatch, Robert B (Journal of Experimental Marine Biology and Ecology, 2007)
Keywords: Ascidiacea; Ascidians; Asexual; Didemnum sp.; Didemnum sp. A; Dispersal; Fragments; Invasive; Reproduction; asexual reproduction; biological invasion; dept.bio; dispersal; invasive species; settling behavior; substrate; vertebrate

Formulations comprising extracts from primitive plant species (mosses, ferns and lichens) to treat and prevent cancers - Crawford, Sarah; Boisvert, Erin (2007)
Keywords: dept.bio; ⛔ No DOI found

Identification of novel cell components designated “tissue organizing structures”* with potential applications in cancer prevention/therapeutics, tissue bioengineering, and gene therapy - Crawford, Sarah; Herbert, Tasino; Potter, Herbert (Cancer Epidemiology and Prevention Biomarkers, 2007)
Keywords: dept.bio; ⛔ No DOI found

Life history of the northern mayfly Baetis bundyae in Rankin Inlet, Nunavut, Canada, with updates to the list of mayflies of Nunavut - Giberson, Donna J; Burian, Steven K; Shouldice, Michael (Canadian Entomologist, 2007)
Mayflies (Ephemeroptera) were collected from 35 sites (streams and tundra ponds) across southern Nunavut in 2002-2005. Nine mayfly species were previously reported for Nunavut: Acentrella feropagus Alba-Tercedor and McCafferty, Acerpenna pygmaea (Hagen), Baetis bundyae Lehmkuhl, B. flavistriga McDunnough, B. foemina McDunnough, Diphetor hageni (Eaton) (Baetidae), Ephemerella aurivillii (Bengtsson) (Ephemerellidae), Leptophlebia nebulosa (Walker) (Leptophlebiidae), and Metretopus borealis (Eaton) (Metrotopidae). We add 7 species to this list, bringing the total to 16: Ameletus inopinatus Eaton (Ameletidae), Acentrella lapponica Bengtsson, Baetis hudsonicus Ide, B. tricaudatus Dodds, Heptagenia solitaria McDunnough (Heptageniidae), Rhithrogena jejuna Eaton (Heptageniidae), and Parameletus chelifer Bengtsson (Siphlonuridae). Based on numbers collected, the dominant mayfly family was Baetidae. Baetis bundyae was the most common mayfly collected, particularly in coastal areas, where larvae were found in permanent and temporary streams and in small or shallow tundra ponds. Larvae hatched 2-3 weeks after ice-out and developed rapidly in 2.5-4 weeks, emerging as adults by early August. All populations containing larvae that were large enough to sex showed female-biased sex ratios, suggesting parthenogenesis. A combination of freeze-tolerant eggs, good dispersal ability, and probable parthenogenesis is probably responsible for the success of Baetidae across the Arctic. © 2007 Entomological Society of Canada.
Keywords: Acentrella feropagus; Acentrella lapponica; Acerpenna pygmaea; Ameletidae; Ameletus inopinatus; Baetidae; Baetis bundyae; Baetis hudsonicus; Canada; Diphetor hageni; Ephemerella aurivillii; Ephemerellidae; Ephemeroptera; Heptagenia solitaria; Heptageniidae; Leptophlebia nebulosa; Leptophlebiidae; Metretopus borealis; North America; Nunavut; Parameletus chelifer; Rhithrogena jejuna; Siphlonuridae; dept.bio; life history; mayfly; parthenogenesis

The size of the nucleus increases as yeast cells grow - Jorgensen, Paul; Edgington, Nicholas P; Schneider, Brandt L; Rupes, Ivan; Tyers, Mike; Futcher, Bruce (Molecular Biology of the Cell, 2007)
It is not known how the volume of the cell nucleus is set, nor how the ratio of nuclear volume to cell volume (N/C) is determined. Here, we have measured the size of the nucleus in growing cells of the budding yeast Saccharomyces cerevisiae. Analysis of mutant yeast strains spanning a range of cell sizes revealed that the ratio of average nuclear volume to average cell volume was quite consistent, with nuclear volume being ∼7% that of cell volume. At the single cell level, nuclear and cell size were strongly correlated in growing wild-type cells, as determined by three different microscopic approaches. Even in G1-phase, nuclear volume grew, although it did not grow quite as fast as overall cell volume. DNA content did not appear to have any immediate, direct influence on nuclear size, in that nuclear size did not increase sharply during S-phase. The maintenance of nuclear size did not require continuous growth or ribosome biogenesis, as starvation and rapamycin treatment had little immediate impact on nuclear size. Blocking the nuclear export of new ribosomal subunits, among other proteins and RNAs, with leptomycin B also had no obvious effect on nuclear size. Nuclear expansion must now be factored into conceptual and mathematical models of budding yeast growth and division. These results raise questions as to the unknown force(s) that expand the nucleus as yeast cells grow. © 2007 by The American Society for Cell Biology.
Keywords: Active Transport, Cell Nucleus; Cell Nucleolus; Cell Nucleus; Cell Size; DNA content; Green Fluorescent Proteins; Karyopherins; Microscopy, Electron; Mutation; Nuclear Localization Signals; Organelle Size; RNA transport; Receptors, Cytoplasmic and Nuclear; Ribosomes; Saccharomyces cerevisiae; Saccharomycetales; article; cell cycle G1 phase; cell division; cell nucleus; cell volume; dept.bio; fungal cell; fungal strain; fungus growth; leptomycin B; mathematical model; mutant; nonhuman; priority journal; protein transport; ribosome subunit; wild type

The mayflies (ephemeroptera) of new hampshire: seasonality and diversity of the stream fauna - Chandler, Donald S; Whitmore, Greg D; Burian, Steven K; Burger, John F (Transactions of The American Entomological Society, 2006)
Season-long sampling in streams and rivers produced 112 species of mayflies, which with other records totals 121 species for New Hampshire; 88 of these are new state records. Appearance of blackwing/mature larvae were used to develop statements on seasonality of species. Distinct differences were found between the faunas of southern and north-central New Hampshire, with an important factor being water temperatures through the season. A biogeographic analysis coupled with known habitat preferences reinforced the hypothesis that water temperature was a critical factor in determining species distributions in the state.
Keywords: Ephemeroptera; dept.bio

Development of synapses and expression of a voltage-gated potassium channel in chick embryonic auditory nuclei. - Feng, Jane J; Morest, D Kent (Hearing research, 2006)
The potassium channel protein, Kv3.1, is abundantly expressed in the chick auditory pathway. Its b-isoform is found in nucleus magnocellularis, which receives the cochlear input, both before and after the establishment of synaptic connections. It is also present in cell cultures in the absence of any peripheral input. However, the expression of this isoform in the embryo has been shown to increase with development. Here, we address the question of the correlation between maturation of synapses in the auditory pathway and the pattern of expression of the b-isoform in a series of embryos prepared for immunohistochemistry at Hamburger-Hamilton stages equivalent to E10, E12, E14, and E17. We show here that this subunit translocates from the perinuclear cytoplasm to the cell membrane domain in nucleus magnocellularis at the time that cochlear nerve endings emerge as endbulbs of Held (E17). In nucleus laminaris, by this time, while abundant Kv3.1b occurs in the perinuclear cytoplasm, a translocation to the cell membrane domain has not yet occurred, and the mature peri-synaptic localization is delayed to a later stage. This difference suggests a hierarchy in the developmental expression of Kv3.1. An unexpected finding is the expression of the a-isoform of Kv3.1 in astrocytes, especially those which surround the developing nuclei and their connecting fibers. We also report here for the first time the presence of Kv3.1b in the initial segments of axons at the times when they begin to form. Our observations suggest that the Kv3.1 channel protein is regulated through mechanisms linked to the development of synaptic activity.
Keywords: *Cochlear Nucleus/me [Metabolism]; *Olivary Nucleus/ph [Physiology]; *Shaw Potassium Channels/ph [Physiology]; *Synapses/ph [Physiology]; Animals; Astrocyte; Astrocytes; Astrocytes/me [Metabolism]; Astrocytes/ph [Physiology]; Axon initial segment; Chick Embryo; Cochlear Nerve; Cochlear Nerve/em [Embryology]; Cochlear Nerve/me [Metabolism]; Cochlear Nucleus; Cochlear Nucleus/em [Embryology]; Gene Expression Regulation, Developmental; Immunohistochemistry; Kv3.1; Neurons; Neurons/me [Metabolism]; Nucleus laminaris; Nucleus magnocellularis; Olivary Nucleus; Olivary Nucleus/em [Embryology]; Shaw Potassium Channels; Shaw Potassium Channels/me [Metabolism]; Synapses; Translocation; animal tissue; article; astrocyte; auditory nervous system; cell membrane; cellular distribution; chick embryo; chronology; cochlear nerve; controlled study; correlation analysis; cytoplasm; dept.bio; developmental stage; embryo; embryo development; immunohistochemistry; intracellular transport; isoprotein; magnocellular nucleus; maturation; nerve ending; nerve fiber; nervous system development; nonhuman; priority journal; protein content; protein determination; protein domain; protein localization; protein subunit; protein transport; regulatory mechanism; synapse; synaptogenesis; thalamus intralaminar nucleus; voltage gated potassium channel